Replacement of Sisal Fiber with Jute Fiber in the Production of Plaster of Paris (POP) Ceiling Boards - Usiju. S. Francis; Mohammad B. Yawale; Abdulhameed U. Abubakar; Ismail A. Yahya; Yazid Aliyu; Murtala M. Hassan; Mamman Hamadu (Journal of Advanced Industrial Technology and Application, 2025)
Plaster of Paris (POP) ceiling boards production is reported to be too expensive, this hinder affordability especially to low-income earners in Nigeria. It high cost is attributed to importation of its constituent materials (Gypsum cement and Sisal fiber). This study assessed the performance of jute fiber as compare to sisal fiber in POP ceiling production. Sisal fiber is imported and sold at exorbitant price within the country. The materials used in this study includes gypsum cement, sisal and jute fibers. The jute fiber was obtained from jute stalks bought from Girei market in Girei LGA Adamawa State, Nigeria. These stalks were retted using tank retting method, and fibers obtained were chemically modified. Specimens were prepared and tested using standard methods outlined in ASTM C 473 – 07 (2009). Flexural strength, nail pull resistance and water absorption of the specimens were determined. Use of jute fiber as reinforcement in POP ceiling boards was found to enhance flexural strength and nail-pull resistance by 4% and 3% respectively. The water absorption of sisal and jute fibers specimens are 6% and 7% which are all within ASTM C1396M-11 (2004) specified maximum limit. Hence jute fiber is considered a suitable alternative to sisal fiber in POP ceiling production Nigeria.